2021
DOI: 10.1038/s42003-021-02598-w
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of environmental conditions, and allelic variation of cytosolic glutamine synthetase on maize hybrid kernel production

Abstract: Cytosolic glutamine synthetase (GS1) is the enzyme mainly responsible of ammonium assimilation and reassimilation in maize leaves. The agronomic potential of GS1 in maize kernel production was investigated by examining the impact of an overexpression of the enzyme in the leaf cells. Transgenic hybrids exhibiting a three-fold increase in leaf GS activity were produced and characterized using plants grown in the field. Several independent hybrids overexpressing Gln1-3, a gene encoding cytosolic (GS1), in the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Cytosolic GS isoforms are mostly involved in primary N assimilation in roots and N remobilization and translocation in shoots (Thomsen et al., 2014). As such, it has been shown that they play a key role during plant growth and development, notably for biomass and storage organ production (Xu et al., 2012; Krapp, 2015; Havé et al., 2017; Amiour et al., 2021). In conifers, as a result of the absence of GS2, studies have focused on GS1a and GS1b, which are each encoded by a single gene.…”
Section: Introductionmentioning
confidence: 99%
“…Cytosolic GS isoforms are mostly involved in primary N assimilation in roots and N remobilization and translocation in shoots (Thomsen et al., 2014). As such, it has been shown that they play a key role during plant growth and development, notably for biomass and storage organ production (Xu et al., 2012; Krapp, 2015; Havé et al., 2017; Amiour et al., 2021). In conifers, as a result of the absence of GS2, studies have focused on GS1a and GS1b, which are each encoded by a single gene.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these transgenic plants had an increased chlorophyll content and photosynthesis efficiency, suggesting that the improved transfer of photosynthate from vegetative organs supports photosynthesis at the reproductive stage and slows down leaf senescence [142]. The overexpression of Gln1-3 in the leaf and bundle sheath mesophyll cells of maize permitted an increase in kernel yield, which was mostly dependent upon the environmental conditions [143].…”
Section: Transgenic Cereals Overexpressing Gs or Gogatmentioning
confidence: 99%
“…In Urriola et al [ 97 ], the biomass and yield of sorghum plants overexpressing a cytosolic GS ( Gln1 ) gene under control of a pUbi differed significantly between greenhouse experiments in winter and spring. The environmental effect on NUE was later demonstrated in extensive field trials (over 5 years in ten different locations) on maize overexpressing two copies of a Gln1-3 (GS1) gene in the mesophyll cells (CsVMV promoter) and in the bundle sheet (RbcS promoter) [ 103 ]. The yield of transgenic plants increased by an average of 3.8%, but this increase depended on both environmental conditions and the transgenic line used.…”
Section: Genetic Engineering Of Nitrogen Metabolismmentioning
confidence: 99%